THUR 154 NMDAR-AB encephalitis: frequency of diagnosis and outcomes. Issue 10 (13th September 2018) - H, Lim; D, Whittam; E, Jackson; N, Williams; D, O'Connell; C, Chadwick; G, Keir; S, Huda; A, Jacob
Abstract : Background: The association of N-methyl d-aspartate receptor-antibodies (NMDAR-Abs) and encephalitis is now well recognised. Methods: Retrospective review of frequency of diagnosis and outcomes in encephalitis with NMDAR-Abs identified at the Walton Centre between 2012–2017. Results: NMDAR-Abs were detected in 29/1131 (3%) of sera and/or CSF samples. Of 20 (69%) patients with encephalitis, 50% were identified in the last two years. Median onset age was 34(17–75) years and 60% (12/20) were female. Median symptom duration before diagnosis was 24(2–720) weeks between 2012–2015, improving to 14(1–96) weeks between 2015–2016. Five patients (25%) had an infectious prodrome (one prior HSV-1 encephalitis). Psychiatric/cognitive symptoms, seizures, and movement disorders were present in 80% (16/20), 70% (14/20), and 55% (11/20) of patients respectively. Three patients had ovarian teratomas. Electroencephalograms were abnormal in 65% (15/23) and MRI brain in 37% (7/19) patients. Unmatched intrathecal oligoclonal bands and CSF pleocytosis were present in 31% (5/16) and 60% (15/25) of samples respectively. Immunotherapy was beneficial in 73% (11/15) of patients. Two patients died (sepsis and multi-organ failure) and two improved spontaneously. At a median follow-up of 9 (5–180) months, 69% (11/16) of patients had an mRS ≤2. Conclusion: Although the recognition of NMDAR-Ab encephalitis has improved, there is still a significant delay to diagnosis. The majority of patients have good outcomes.